GREEN ECONOMY AS A FACTOR OF SUSTAINABLE DEVELOPMENT - Inna Tomashuk; Vasyl Baldynyuk; Liudmyla Boltovska (Baltic Journal of Economic Studies, 2023)
The purpose of the article is to study the directions of development of the green economy in Ukraine as a factor of ensuring the transition to sustainable development of the country. Methodology. One of the main elements of the methodology for conducting research on the green economy as a factor of ensuring sustainable development are evaluation methods. Comparative, balance, graphic, economic-mathematical and other methods of economic justification are used in the work. The methods of systematisation and generalisation were used to study the principles of further ecologically balanced development, economic-statistical, structural-logical and analytical – for the development of methods and indicators for the analysis of the system of directions of the green economy, graphic – for the visual presentation of the dynamics of indicators of sustainable development. The results of the work show that the growth of income and employment in the green economy is guaranteed at the expense of public and private investments aimed at increasing energy efficiency, reducing the negative impacts of economic activity and increasing the diversity and productivity of the biosphere, in the interests of the entire population, especially the poorest. It is important to emphasise that the concept of the green economy does not replace the concept of sustainable development, but develops it and is a means of putting it into practice. Green development can only be ensured if environmental and economic policies are integrated in such a way that social progress, economic growth and improvement in the quality of life of the population take place against a background of reduced threats to the surrounding natural environment. Practical implications. The concept of green growth emphasises the importance of integrating environmental and economic policies in order to identify new potential sources of economic growth without placing an "unsustainable" burden on the quantity and quality of natural resources. The transition to a green economy requires the application of a wide range of measures, including economic instruments (taxes, subsidies, emissions trading schemes), government regulatory measures (setting standards) and non-economic measures (voluntary initiatives, provision of information). Value/originality. Important economic indicators of sustainable environmental and economic development are a nature-intensive economy and a structural indicator that reflects the specific weight of products and investments in the natural resource-based sectors of the economy.